Box For Living Business Strategy 7Cs Compass Model Analysis And The Implementation Of Business Model Canvas - Gunawan, Meliesa Florentin; Aldianto, Leo (The Indonesian Journal of Business Administration, 2013)
This research aims to find the root cause of the company with 7Cs Compass Model Analysis combined with IFAS, EFAS, and Fishbone Diagram. The solution in this research is using TOWS Matrix to find the effective strategies for Box For Living, the strategies are : focus to develop their brand image, focus about container modification product, the research and how to deliver the knowledge to public, sharping the diversification strategy and harmonize the development of special products and their diversification product. The implementation of those strategies in Business Model Canvas can describe every aspect of companyâ€™s business model block and the whole mechanism of Box For Living business process.Â Keywords : Container Modification, Building Design Consultation and Construction, 7Cs Compass Model, Business Model Canvas, Diversification Strategy.